Cement-based inorganic terrazzo floor dry powder mortar and preparation method thereof

CN122940424APending Publication Date: 2026-10-20BAUMIT BUILDING MATERIAL (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611054869.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

现有技术中,传统磨石地坪多采用现场拌制,存在配比不稳定、施工效率低、易开裂、耐腐蚀性不足等问题

Benefits of technology

1. 本申请实施例的地面用水泥基无机磨石地坪干粉砂浆,以快硬硫铝酸盐水泥作为凝胶材料,以羟基羧酸和/或其盐类缓凝剂与包括糖类缓凝剂和多羟基醇类缓凝剂的复配多羟基化合物作为缓凝剂体系,使得无机磨石地坪干粉砂浆具备足够可施工时间60min至100min的同时,保证施工后磨石地坪的强度可达到C35等级,并具备成本优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This application discloses a cement-based inorganic terrazzo floor dry powder mortar and its preparation method. The cement-based inorganic terrazzo floor dry powder mortar, by weight, comprises: 290 to 400 parts of rapid-hardening sulfoaluminate cement, 450 to 600 parts of aggregate, 60 to 100 parts of mineral filler, 8 to 15 parts of dispersible latex powder, 2.0 to 3.5 parts of water-reducing agent, 2.0 to 3.0 parts of retarder, 0.8 to 1.2 parts of defoamer, 0.3 to 0.8 parts of cellulose ether, 0.3 to 0.8 parts of early-strength agent, and 0 to 20 parts of pigment; wherein the retarder includes a first retarder and a second retarder; the first retarder is a hydroxycarboxylic acid and / or its salt retarder, and the second retarder includes a sugar retarder, a polyhydroxy alcohol retarder, and additives. This retarder system allows the inorganic terrazzo floor dry powder mortar sufficient time for construction while ensuring that the terrazzo floor strength can reach C35 grade after construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This article relates to building materials technology, particularly to a cement-based inorganic terrazzo floor dry powder mortar and its preparation method, as well as the slurry based on the dry powder mortar. Background Technology

[0002] Cement-based inorganic terrazzo flooring dry powder mortar is a flooring material made by dry mixing cement as a binder and adding selected aggregates and functional admixtures. Currently, traditional terrazzo flooring is mostly mixed on-site, which suffers from problems such as unstable proportions, low construction efficiency, easy cracking, and insufficient corrosion resistance. While conventional dry powder mortar improves construction convenience, it still has limitations in meeting the requirements for seamless construction over large areas (requiring a certain construction time) and integrating mechanical properties with decorative effects. Summary of the Invention

[0003] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.

[0004] Rapid-hardening sulfoaluminate cement is a high-early-strength hydraulic cementitious material made by grinding raw materials of appropriate composition, calcining them to obtain clinker with anhydrous calcium sulfoaluminate and dicalcium silicate as the main mineral components, and grinding them together with a small amount of limestone and an appropriate amount of gypsum. The core minerals of rapid-hardening sulfoaluminate cement are anhydrous calcium sulfoaluminate (C4A3), dicalcium silicate (C2S), and gypsum (C). After water is added for construction, the material rapidly undergoes the main reaction shown in formula (I), quickly generating a large amount of needle-like ettringite (AFt), which overlaps to form a strength skeleton, which is the chemical basis for its rapid hardening and early strength; in the later stage, the secondary reaction shown in formula (II) occurs, filling the structure, and the strength continues to increase in the later stage. If a retarder is not added, rapid-hardening sulfoaluminate cement will initially set within 10 to 20 minutes or even reach a high strength and become unusable for construction.

[0005] C4A3 + 2C + 38H → ettringite (AFt) + alumina (AH3) (I) C2S + H → CSH gel + Ca(OH)2 (II) Retarder is an admixture that prolongs the hydration induction period of cement, keeping the cement paste in a plastic state for a longer time, thereby delaying the initial and final setting times to provide a suitable workable time. Commonly used retarders include sucrose, citric acid, tartaric acid, and sodium gluconate. However, the inventors found that for terrazzo floor dry powder mortar using rapid-hardening sulfoaluminate cement as the gelling material, the retarding effect on rapid-hardening sulfoaluminate cement systems is not ideal when using a single retarder or an unsuitable combination of retarders, especially at high ambient temperatures. For example, using hydroxycarboxylate retarders such as tartaric acid alone can cause the morphology of products such as calcium silicate hydrate (CSH) and ettringite to deteriorate, weaken the overlap, increase porosity, and loosen the structure, thus affecting the overall strength of the material. Polyhydroxy compound retarders such as sucrose have little retarding effect at low dosages, are greatly affected by ambient temperature, and the appropriate dosage is unstable. Increasing the dosage can easily lead to excessively long retarding or burst setting, and significantly increase costs.

[0006] To address the aforementioned issues, this application achieves an ideal retarding effect by using a compounded hydroxycarboxylate retarder and a compounded polyhydroxy compound retarder, thereby obtaining sufficient workable time (60 to 100 minutes). Furthermore, because the compounded retarder reduces the amount of hydroxycarboxylate retarder (such as tartaric acid) required for use alone, it reduces the impact on the early and later strength of the material. This leaves room for the cement, the main source of the material's strength, and allows for a further reduction in the amount of cement required to achieve standard strength while still meeting the overall strength requirements.

[0007] In a first aspect, embodiments of this application provide a cement-based inorganic terrazzo flooring dry powder mortar, which, by weight, comprises the following components: A dry powder mortar for cement-based inorganic terrazzo flooring, characterized in that it comprises the following components by weight: The composition includes: 290 to 400 parts of rapid-hardening sulfoaluminate cement, 450 to 600 parts of aggregate, 60 to 100 parts of mineral filler, 8 to 15 parts of dispersible latex powder, 2.0 to 3.5 parts of water-reducing agent, 2.0 to 3.0 parts of retarder, 0.8 to 1.2 parts of defoamer, 0.3 to 0.8 parts of cellulose ether, 0.3 to 0.8 parts of early-strength agent, and 0 to 20 parts of pigment. The retarder includes a first retarder and a second retarder; the first retarder is a hydroxycarboxylic acid and / or its salt retarder; the second retarder is a compound polyhydroxy alcohol retarder, including sugar retarder, polyhydroxy alcohol retarder and additives.

[0008] Secondly, embodiments of this application also provide a method for preparing the dry powder mortar for cement-based inorganic terrazzo flooring described in the first aspect, comprising: The early strength agent, cellulose ether, defoamer, retarder, water-reducing agent, dispersible latex powder, pigment and mineral filler are mixed evenly to obtain a premix; Mix the rapid-hardening sulfoaluminate cement, aggregate and the premix evenly; The cement-based inorganic terrazzo floor dry powder mortar for the ground is obtained.

[0009] Thirdly, embodiments of this application also provide a cement-based inorganic terrazzo floor dry powder mortar, comprising the cement-based inorganic terrazzo floor dry powder mortar described in the first aspect and water.

[0010] Compared with the prior art, the technical solution of this application has the following beneficial effects: 1. The dry powder mortar for cement-based inorganic terrazzo flooring in this application embodiment uses rapid-hardening sulfoaluminate cement as a gelling material and a compound polyhydroxy compound including sugar retarder and polyhydroxy alcohol retarder as a retarder system. This allows the dry powder mortar for inorganic terrazzo flooring to have a sufficient construction time of 60 to 100 minutes while ensuring that the strength of the terrazzo flooring after construction can reach the C35 grade, and it also has a cost advantage.

[0011] 2. The dry powder mortar for cement-based inorganic terrazzo flooring in this application embodiment achieves high strength, high durability, and longer construction time for the inorganic terrazzo flooring mortar by rationally adjusting the components and their proportions, for example by using heavy calcium carbonate powder and slag powder as mineral fillers. The slag powder undergoes a secondary hydration reaction in the alkaline environment generated by cement hydration, generating CSH gel to fill the capillary pores, forming a synergistic effect of early nucleation and later activation with the heavy calcium carbonate powder.

[0012] 3. The dry powder mortar for cement-based inorganic terrazzo flooring in this application embodiment meets the strength requirements of standard cement-based self-leveling mortar for flooring while controlling the amount of expensive rapid-hardening sulfoaluminate cement and additives such as lithium sulfate.

[0013] Other features and advantages of this application will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the application. Other advantages of this application may be realized and obtained by means of the methods described in the description. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application are described in detail below. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be arbitrarily combined with each other.

[0015] In a first aspect, embodiments of this application provide a cement-based inorganic terrazzo flooring dry powder mortar, which, by weight, comprises the following components: The composition includes: 290 to 400 parts of rapid-hardening sulfoaluminate cement, 450 to 600 parts of aggregate, 60 to 100 parts of mineral filler, 8 to 15 parts of dispersible latex powder, 2.0 to 3.5 parts of water-reducing agent, 2.0 to 3.0 parts of retarder, 0.8 to 1.2 parts of defoamer, 0.3 to 0.8 parts of cellulose ether, 0.3 to 0.8 parts of early-strength agent, and 0 to 20 parts of pigment. The retarder includes a first retarder and a second retarder; the first retarder is a hydroxycarboxylic acid and / or its salt retarder, and the second retarder is a compound polyhydroxy alcohol retarder, including sugar retarder, polyhydroxy alcohol retarder and additives.

[0016] This application uses rapid-hardening sulfoaluminate cement as the gelling material to meet the 24-hour strength requirements (compressive strength ≥15 MPa, flexural strength ≥3 MPa) specified in the T / CSTM 00983-2024 standard "Polymer Modified Cement-Based Terrazzo Flooring Mortar".

[0017] In rapid-setting sulfoaluminate cement gel systems, when hydroxycarboxylic acids and / or their salts are used as retarder, in the highly alkaline environment after water-based construction, the acid radicals will react with Ca... 2+ Al 3+ These retarders form stable chelates, reducing the ion concentration in the liquid phase, delaying hydration, and adsorbing onto the surface of cement minerals to form an organic adsorption layer, inhibiting further hydration and thus exerting a retarding effect. However, such retarders can also cause the morphology of products such as CSH and ettringite to deteriorate and the overlap to weaken, leading to increased porosity and loose structure in the material, thereby affecting the overall strength of the material.

[0018] In rapid-hardening sulfoaluminate cement gel systems, after water addition and application, polyhydroxyl compounds disperse on the surface of cement particles via hydroxyl adsorption. These compounds utilize electrostatic interactions and steric hindrance to delay setting and prolong flow retention. Furthermore, they can interact with Ca... 2+ Weak complexation is achieved, which gently prolongs the induction period. However, polyhydroxy compound retarders such as sucrose have little retarding effect at low addition levels, are greatly affected by ambient temperature, and the appropriate addition amount varies greatly with the environment. Increasing the addition amount can easily lead to excessively long retarding.

[0019] This application utilizes a retarder system formed by combining hydroxycarboxylic acid and / or its salt retarder with a compound polyhydroxy compound retarder that simultaneously contains sugar retarder and polyhydroxy alcohol retarder in a rapid-hardening sulfoaluminate cement gel system. This ensures that the inorganic terrazzo floor dry powder mortar has sufficient workability time (60 min to 100 min) while avoiding abnormal retarding or strength reduction problems caused by a single type of retarder.

[0020] In one exemplary embodiment, the cement-based inorganic terrazzo flooring dry powder mortar, by weight, comprises the following components: The composition includes 290 to 350 parts of rapid-hardening sulfoaluminate cement, 540 to 600 parts of aggregate, 80 to 100 parts of mineral filler, 10 to 15 parts of dispersible latex powder, 2.0 to 3.0 parts of water-reducing agent, 2.0 to 2.8 parts of retarder, 0.8 to 1.2 parts of defoamer, 0.3 to 0.6 parts of cellulose ether, 0.3 to 0.6 parts of early-strength agent, and 0 to 20 parts of pigment.

[0021] In one exemplary embodiment, the hydroxycarboxylic acid and / or its salt retarder as the first retarder is selected from any one or more of tartaric acid or its salt (e.g., sodium tartrate), citric acid or its salt (e.g., sodium citrate), gluconic acid or its salt (e.g., sodium gluconate), malic acid or its salt, salicylic acid, etc., and may be selected as tartaric acid, citric acid or sodium gluconate.

[0022] In one exemplary embodiment, the second retarder, by weight percentage, comprises 45% to 70% of a sugar retarder, 20% to 35% of a polyhydroxy alcohol retarder, and 10% to 25% of an additive.

[0023] In one exemplary embodiment, the second retarder includes a carbohydrate retarder selected from one or more of glucose, fructose, sucrose, lactose, starch, dextrin, molasses, etc. In another exemplary embodiment, the carbohydrate retarder includes glucose and sucrose. The percentage of the carbohydrate retarder's weight to the total weight of the second retarder is, for example, but not limited to, 45%, 48%, 50%, 52%, 55%, 56%, 57%, 58%, 59%, 60%, 62%, 64%, 65%, 68%, or 70%.

[0024] In one exemplary embodiment, the second retarder comprises a polyhydroxy alcohol retarder selected from any one or more of glycerol, sorbitol, xylitol, mannitol, polyvinyl alcohol, erythritol, isomaltitol, etc. In another exemplary embodiment, the polyhydroxy alcohol retarder includes sorbitol and xylitol. The percentage of the weight of the polyhydroxy alcohol retarder to the total weight of the second retarder is, for example, but not limited to, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 35%.

[0025] In one exemplary embodiment, the adjuvant in the second retarder is selected from any one or more of dispersants, stabilizers, and synergists. The dispersant may be selected from any one or more of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, sodium lignosulfonate, calcium lignosulfonate, naphthalene sulfonate formaldehyde condensate, polycarboxylate ether water-reducing agents (such as methacrylic acid-polyethylene glycol monomethyl ether copolymer), sodium dodecylbenzene sulfonate, and fatty alcohol polyoxyethylene ether; the stabilizer may be selected from any one or more of xanthan gum, fentanyl gum, cellulose ethers (such as hydroxypropyl methylcellulose and hydroxyethyl cellulose), polyacrylamide, sodium bentonite, attapulgite, fumed silica, disodium ethylenediaminetetraacetate, and sodium gluconate; the synergist may be selected from any one or more of sodium tripolyphosphate (which also has dispersing and auxiliary retarding functions), aminotrimethylene phosphonic acid, soluble borates, and zinc salts. In one exemplary embodiment, the percentage of the weight of the adjuvant to the total weight of the second retarder is, for example, but not limited to, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 2%, 21%, 22%, 23%, 24%, or 25%.

[0026] In one exemplary embodiment, the percentage of the total weight of the retarder to the weight of the rapid-hardening sulfoaluminate cement is 0.6% to 0.9%, such as, but not limited to, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, and 0.9%.

[0027] In one exemplary embodiment, the weight ratio of the first retarder and the second retarder is 1:(1.0 to 1.5), such as, but not limited to, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, and optionally 1:(1.3 to 1.4). Within the above ratio range, the retarding effect of the retarder system is significant and stable. However, when there is too much polyhydroxy compound retarder, the retarding effect is poor and the cost pressure is high. When there is too much hydroxycarboxylic acid and / or its salt retarder, the retarding effect will fluctuate significantly with temperature and have a significant impact on the later strength.

[0028] In one exemplary embodiment, the first retarder is tartaric acid, citric acid, or sodium gluconate.

[0029] In one exemplary embodiment, the second retarder, by weight percentage, comprises 28% to 42% sucrose, 18% to 27% glucose, 14% to 22% sorbitol, 6% to 13% xylitol, 4% to 10% sodium tripolyphosphate, and 6% to 15% sodium lignosulfonate. In another exemplary embodiment, the second retarder, by weight percentage, comprises 35% sucrose, 22% glucose, 18% sorbitol, 10% xylitol, 6% sodium tripolyphosphate, and 9% sodium lignosulfonate.

[0030] In one exemplary embodiment, the rapid-hardening sulfoaluminate cement is selected from white rapid-hardening sulfoaluminate cement or gray rapid-hardening sulfoaluminate cement.

[0031] In cement-based inorganic terrazzo flooring, aggregates mainly form a rigid support structure by stacking aggregate particles together, which can restrain the chemical shrinkage and drying shrinkage generated during the hardening process of cement paste and reduce the risk of cracking.

[0032] In one exemplary embodiment, the aggregate is selected from one or more of manufactured sand, quartz sand, and river sand. In one exemplary embodiment, the aggregate has a particle size of 0.1 mm to 2.4 mm. In one exemplary embodiment, the aggregate is quartz sand, and by weight, its particle size distribution includes 150 to 200 parts of quartz sand with a particle size of 2.4 mm to 0.85 mm, 140 to 180 parts of quartz sand with a particle size of 0.85 mm to 0.425 mm, 130 to 170 parts of quartz sand with a particle size of 0.425 mm to 0.212 mm, and 50 to 100 parts of quartz sand with a particle size of 0.212 mm to 0.1 mm. Through the above-mentioned gradation design, the aggregate packing significantly reduces the porosity, reducing the need for cement slurry to fill voids, while the formed skeleton support structure effectively improves the wear resistance and compressive strength of the floor.

[0033] Mineral fillers are used to provide physical filling and / or hydration nucleation sites.

[0034] In one exemplary embodiment, the mineral filler is selected from any one or more of calcium carbonate powder, slag powder, talc powder, wollastonite powder, and mica powder. In one exemplary embodiment, the calcium carbonate powder is selected from any one or more of heavy calcium carbonate powder, light calcium carbonate powder, and limestone powder, and may be selected as heavy calcium carbonate powder. In one exemplary embodiment, the heavy calcium carbonate powder has a CaCO3 content of 95% to 99% and a particle size of 1 μm to 70 μm.

[0035] In one exemplary embodiment, the slag powder is, for example, but not limited to, S75, S95, or S105 grade slag powder classified according to the standard "Granulated Blast Furnace Slag Powder for Cement and Concrete" (GB / T 18046), and may be selected as S95 grade slag powder. In one exemplary embodiment, the specific surface area of ​​the S95 grade slag powder is ≥400 m². 2 / kg, 28-day activity index ≥95%, moisture content ≤1.0%, flowability ratio ≥95%, particle size 1 μm to 60 μm; S95 grade slag powder, by weight, includes: 30 to 75 parts CaO, 28 to 38 parts SiO2, 8 to 18 parts Al2O3, 5 to 12 parts MgO, 0.1 to 2 parts MnO, and 0.1 to 3 parts sulfides.

[0036] In one exemplary embodiment, the mineral filler is heavy calcium carbonate powder.

[0037] In one exemplary embodiment, the mineral filler is heavy calcium carbonate powder and slag powder, with a mass ratio of 1:(0.5 to 2), such as, but not limited to, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0, and optionally 1:(0.8 to 1.2). During cement hydration, when heavy calcium carbonate powder and slag powder are used together as mineral fillers, heavy calcium carbonate powder provides nucleation sites in the early stages, promoting the uniform distribution of ettringite; slag powder is activated in the middle and later stages, compensating for the potential strength loss in the later stages due to the introduction of retarders. The simultaneous use of both can achieve a balance between early and later strength. At the same time, heavy calcium carbonate powder (typical particle size of 1 μm to 70 μm), slag powder (typical particle size of 1 μm to 60 μm), and cement particles (3 μm to 60 μm) can form a multi-level gradation filling effect, significantly increasing the bulk density of solid particles, reducing the filling water requirement, and reducing capillary volume. It can also significantly reduce the porosity and number of interconnected pores in the hardened body, which is macroscopically manifested as an improvement in impermeability, wear resistance, and freeze-thaw resistance.

[0038] Dispersible latex powder, used as a binder, rapidly disperses into the water when dry mortar is mixed with water, forming a stable polymer emulsion. During cement hydration, it forms a polymer film, which, together with hydration products such as ettringite, forms an interpenetrating network structure, significantly improving the mortar's bonding strength and flexural strength. At the same time, the polymer film fills the capillary pores, enhancing the mortar's wear resistance and impermeability, giving terrazzo flooring excellent long-term durability.

[0039] In one exemplary embodiment, the dispersible latex powder is selected from one or more of the following: vinyl acetate-ethylene copolymer, vinyl acetate, ethylene, and higher fatty acid vinyl ester terpolymer dispersible latex powder, vinyl acetate and higher fatty acid vinyl ester copolymer dispersible latex powder, vinyl acetate, acrylate, and higher fatty acid vinyl ester terpolymer dispersible latex powder. Optionally, the dispersible latex powder is a vinyl acetate-ethylene copolymer, which has a relatively small impact on the rheological properties of the mortar.

[0040] Water-reducing agents are used to disperse cement particles, reduce the unit water consumption of dry mortar, and improve its fluidity.

[0041] In one exemplary embodiment, the water-reducing agent is selected from one or more of polycarboxylate superplasticizers (PCE), aminosulfonate superplasticizers, aliphatic superplasticizers, lignin sulfonate superplasticizers, naphthalene-based superplasticizers (FDN superplasticizers), and melamine-based superplasticizers (SM), with polycarboxylate superplasticizers (PCE) being the preferred choice. On one hand, the polycarboxylate superplasticizer can adsorb onto the surface of rapid-hardening sulfoaluminate cement particles through steric hindrance, effectively reducing interparticle friction, releasing encapsulated free water, and significantly improving mortar fluidity (initial fluidity ≥ 210 mm) at the initial water content. Simultaneously, its slow-release molecular structure forms a competitive adsorption equilibrium with the first and second retarders, synergistically maintaining fluidity stability within a 60-100 minute workable time (20-minute fluidity loss ≤ 20%). On the other hand, the polycarboxylate superplasticizer reduces the water-cement ratio to 0.20-0.25, promoting a reduction in slurry capillary pores and densification of the interfacial transition zone. In addition, polycarboxylate-based high-efficiency water-reducing agents can work synergistically with heavy calcium carbonate powder and dispersible latex powder to reduce the viscosity of the slurry while ensuring the expulsion of air bubbles. They can also make pigments dispersed evenly, resulting in a dense, color-different, and pinhole-free surface for hardened terrazzo flooring, which combines high strength and high decorative properties.

[0042] Defoamers can quickly eliminate tiny air bubbles introduced by dispersible latex powder and water-reducing agents during mortar mixing, resulting in a dense, pinhole-free surface for hardened terrazzo flooring, while avoiding adverse effects on the mortar's fluidity and mechanical properties.

[0043] In one exemplary embodiment, the defoamer is selected from any one or more of polysiloxane defoamers, polyether defoamers, polyether-modified silicone defoamers, tributyl phosphate, mineral oil defoamers, and alkynyl alcohol defoamers, and may be selected as a polyether-modified silicone defoamer.

[0044] Cellulose ethers have high water retention and thickening effects in mortar. While ensuring the excellent workability and fluidity of the mortar, they provide a sufficient liquid phase environment for cement hydration, ensuring the strength and appearance quality of the hardened terrazzo floor.

[0045] In one exemplary embodiment, the cellulose ether is selected from any one or more of methylcellulose ether, hydroxypropyl methylcellulose ether, and carboxymethylcellulose ether, and may be selected as hydroxypropyl methylcellulose ether.

[0046] In one exemplary embodiment, the early-strength agent is selected from any one or more of lithium sulfate, lithium hydroxide, lithium carbonate, lithium silicate, lithium chloride, and aluminum sulfate, and may be lithium sulfate. The aforementioned early-strength agent can synergistically control the cement setting process with the composite retarder system to meet the 24-hour strength requirements of the material.

[0047] Pigments are used to adjust the color of mortar to achieve a decorative effect. In one exemplary embodiment, the pigment is selected from any one or more of titanium dioxide, iron oxide red, iron oxide yellow, iron oxide black, chromium oxide green, cobalt blue, ultramarine, manganese oxide, chromium oxide, ochre, Prussian red, and mica. In another exemplary embodiment, the pigment is titanium dioxide, wherein the TiO2 content is 90% to 98%.

[0048] Secondly, embodiments of this application provide a method for preparing the dry powder mortar for cement-based inorganic terrazzo flooring described in the first aspect, comprising: The early strength agent, cellulose ether, defoamer, retarder, water-reducing agent, dispersible latex powder, pigment and mineral filler are mixed evenly to obtain a premix; Mix the rapid-hardening sulfoaluminate cement, aggregate and the premix evenly; The cement-based inorganic terrazzo floor dry powder mortar for the ground is obtained.

[0049] Thirdly, embodiments of this application also provide a cement-based inorganic terrazzo floor dry powder mortar, comprising the cement-based inorganic terrazzo floor dry powder mortar described in the first aspect or the cement-based inorganic terrazzo floor dry powder mortar prepared by the preparation method described in the second aspect, and water.

[0050] In one exemplary embodiment, the mass ratio of the cement-based inorganic terrazzo floor dry powder mortar to water is 1:(0.12 to 0.14).

[0051] Unless otherwise specified, all materials used in the following embodiments are commercially available. The specific materials used in the following embodiments are as follows: White rapid-hardening sulfoaluminate cement was purchased from Tangshan Arctic Bear Building Materials Co., Ltd., with specifications of WR SAC 42.5. It contains 10% to 18% gypsum, has a loss on ignition ≤3.0%, and a specific surface area ≥400 m². 2 / kg.

[0052] The aggregate, quartz sand, was purchased from Kunshan Skawi Trading Co., Ltd., with a particle size of 0.1 mm to 2.4 mm, a mud content of ≤0.1%, a mud lump content of ≤0.1%, a flaky particle content of ≤1%, and an apparent density of ≥2500 kg / m³. 3 .

[0053] The heavy calcium carbonate powder was purchased from Anhui Zhongshi Building Materials Co., Ltd., with CaCO3 accounting for 95% to 99%, and is 325 mesh.

[0054] S95 grade slag powder was purchased from Shanghai Baotian New Building Materials Co., Ltd., and the specific surface area of ​​the S95 grade slag powder is ≥400 m². 2 / kg, 28d activity index ≥95%, moisture content ≤1.0%, particle size 1 μm to 60 μm, its composition includes: 30 to 75 parts CaO, 28 to 38 parts SiO2, 8 to 18 parts Al2O3, 5 to 12 parts MgO, 0.1 to 2 parts MnO, and 0.1 to 3 parts sulfides.

[0055] The titanium dioxide was purchased from Shanghai Yuejiang Titanium Dioxide Chemical Co., Ltd., with TiO2 accounting for 90% to 98% and particle size ranging from 0.2 μm to 0.4 μm.

[0056] The dispersible latex powder is a vinyl acetate-ethylene copolymer dispersible latex powder, purchased from Wacker Chemie (Nanjing) Co., Ltd., model: VINNAPAS ® 4115N, ash content: 13% to 14.5%, bulk density: 490 g / L to 590 g / L.

[0057] The polycarboxylate superplasticizer (PCE) was purchased from Shanghai Shenhua New Material Technology Co., Ltd., model: PC-100.

[0058] The aminosulfonate-based high-efficiency water-reducing agent was purchased from Nanjing Yifan Building Materials Industry Co., Ltd., model number: YF-1.

[0059] Tartaric acid, a retarder, was purchased from Shanghai Shenhua New Material Technology Co., Ltd.; citric acid, a retarder, was purchased from Tianjin Kebang New Material Co., Ltd.; sodium gluconate, a retarder, was purchased from Tianjin Kebang New Material Co., Ltd.; and sucrose, a retarder, was purchased from Tianjin Kemeio Chemical Reagent Co., Ltd.

[0060] The compound polyhydroxy alcohol retarder is composed of the following components by weight: 35 parts sucrose, 22 parts glucose, 18 parts sorbitol, 10 parts xylitol, 6 parts sodium tripolyphosphate, and 9 parts sodium lignosulfonate.

[0061] Glucose and sorbitol were purchased from Suzhou Minghua Sugar Alcohol Co., Ltd.; xylitol was purchased from Suzhou Kening Polyol Co., Ltd.; sodium tripolyphosphate and sodium lignosulfonate were purchased from Wujiang Runtian Fine Chemical Co., Ltd.

[0062] Glucose, sorbitol, xylitol, sodium tripolyphosphate, and sodium lignosulfonate were all purchased from Tianjin Kebang New Materials Co., Ltd.

[0063] The defoamer was a polyether-modified silicone defoamer purchased from Shanghai Shenhua New Material Technology Co., Ltd., model: DF-94.

[0064] The cellulose ether is hydroxypropyl methylcellulose ether, purchased from Zhejiang Meixinjia Zhongwei Pharmaceutical Co., Ltd., model: Mk-400, viscosity: 350 mPa·s to 450 mPa·s, water content ≤8%.

[0065] The lithium sulfate was purchased from Shanghai Shenhua New Material Technology Co., Ltd., industrial grade, with a Li2SO4 content of ≥98.5% and a moisture content of ≤1%.

[0066] Example 1 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of tartaric acid, 1.4 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0067] Example 2 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 parts by weight of defoamer, 1.2 parts by weight of tartaric acid, 1.6 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 20 parts by weight of heavy calcium carbonate powder, 20 parts by weight of slag powder, and 20 parts by weight of heavy calcium carbonate powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 350 parts by weight of white rapid-hardening sulfoaluminate cement, 190.6 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 69.4 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0068] Example 3 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of citric acid, 1.4 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0069] Example 4 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of sodium gluconate, 1.4 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0070] Example 5 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of tartaric acid, 1.4 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, and 90 parts by weight of heavy calcium carbonate powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0071] Example 6 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 0.8 parts by weight of tartaric acid, 1.0 part by weight of compound polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80.6 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 118.4 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0072] Example 7 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 0.8 parts by weight of tartaric acid, 1.0 part by weight of compound polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80.6 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 118.4 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0073] Example 8 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.2 parts by weight of tartaric acid, 1.5 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 79.7 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119.3 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0074] Example 9 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.2 parts by weight of tartaric acid, 1.5 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 79.7 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119.3 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0075] Example 10 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of tartaric acid, 1.4 parts by weight of compound polyhydroxy alcohol retarder, 2.8 parts by weight of aminosulfonate-based high-efficiency water-reducing agent, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0076] Comparative Example 1 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.5 parts by weight of tartaric acid, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80.9 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 118.1 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0077] Comparative Example 2 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 2.0 parts by weight of tartaric acid, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80.4 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 118.6 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0078] Comparative Example 3 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 2.4 parts by weight of tartaric acid, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0079] Comparative Example 4 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 2.4 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0080] Comparative Example 5 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 2.4 parts by weight of sucrose, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0081] Comparative Example 6 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of citric acid, 1.4 parts by weight of sodium gluconate, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0082] Comparative Example 7 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of tartaric acid, 1.4 parts by weight of sodium gluconate, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0083] Comparative Example 8 0.4 parts by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of tartaric acid, 1.4 parts by weight of sucrose, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 191 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0084] Comparative Example 9 1.0 part by weight of lithium sulfate, 0.4 parts by weight of cellulose ether, 1.0 part by weight of defoamer, 1.0 part by weight of tartaric acid, 1.4 parts by weight of compounded polyhydroxy alcohol retarder, 2.8 parts by weight of polycarboxylate superplasticizer, 12 parts by weight of dispersible latex powder, 10 parts by weight of titanium dioxide, 45 parts by weight of heavy calcium carbonate powder, and 45 parts by weight of slag powder are added to a mixer in sequence for premixing. After mixing evenly, a premix is ​​obtained. Then, 300 parts by weight of white rapid-hardening sulfoaluminate cement, 190.4 parts by weight of 2.4 mm to 0.85 mm quartz sand, 160 parts by weight of 0.85 mm to 0.425 mm quartz sand, 150 parts by weight of 0.425 mm to 0.212 mm quartz sand, 80 parts by weight of 0.212 mm to 0.1 mm quartz sand, and 119.6 parts by weight of premixed material are sequentially measured and added to a mixer for mixing. After mixing evenly, the cement-based inorganic terrazzo floor dry powder mortar is obtained.

[0085] Performance testing The cement-based inorganic terrazzo floor dry powder mortars prepared in the examples and comparative examples were mixed with water at a mass ratio of 1:0.13. After thorough mixing, the mixture was tested according to the Chinese building materials industry standard T / CSTM 00983-2024 "Polymer-Modified Cement-Based Terrazzo Floor Mortar". The standard test conditions and curing conditions were as follows: Standard test conditions and curing conditions for Examples 1-5 and 10, and Comparative Examples 1-9: temperature (23±2)℃, relative humidity (50±5)%; Simulated summer test conditions and curing conditions for Examples 6 and 8: temperature (30±2)℃, relative humidity (50±5)%; Simulated winter test conditions and curing conditions for Examples 7 and 9: temperature (10±2)℃, relative humidity (50±5)%. The test results are shown in Tables 1 to 4 below.

[0086] Table 1 Table 2 Table 3 Table 4 As shown in Tables 1 and 2, the physical properties of the cement-based inorganic terrazzo floor dry powder mortars prepared in Examples 1-10 all meet the technical requirements for cement-based floor mortar products in T / CSTM 00983-2024 "Polymer-Modified Cement-Based Terrazzo Floor Mortar". Based on the 20-minute flowability loss and subsequent strength results, Examples 1 and 2, using a retarder system including tartaric acid and a compounded polyhydroxy alcohol retarder at a dosage of 0.8% of the rapid-hardening sulfur-aluminum cement, exhibited excellent workability and strength effects. Compared to Example 1, Examples 3 and 4, by replacing tartaric acid with other hydroxycarboxylate retarders (citric acid or sodium gluconate), also met the workability requirements. In Example 5, the filler was replaced with only heavy calcium carbonate powder, which lacked the secondary reaction of mineral powder. The overall strength was slightly lower than that of Example 1. In Example 1, the sulfur ions released by the added mineral powder also helped to extend the construction time. After hardening, the mineral powder and calcium hydroxide were hydrated again when they came into contact with water, generating additional hydrated calcium silicate and hydrated calcium aluminate, which further enhanced the bonding strength.

[0087] Examples 6 and 7 used a retarder system comprising tartaric acid and a compounded polyhydroxy alcohol retarder at 0.6% of the rapid-hardening sulfoaluminate cement, exhibiting high workability and strength grades in both summer and winter. Examples 8 and 9 used a retarder system comprising tartaric acid and a compounded polyhydroxy alcohol retarder at 0.9% of the rapid-hardening sulfoaluminate cement, also demonstrating high workability and meeting standard strength grades in both summer and winter. Example 10, using an aminosulfonate-based high-efficiency water-reducing agent, showed a slight decrease in overall strength and shrinkage compared to the sample using a polycarboxylate-based high-efficiency water-reducing agent, but still met standard requirements.

[0088] As shown in Tables 3 and 4, Comparative Examples 1, 2, and 3, when using only tartaric acid as a retarder, were added in a gradient manner, and it was found that they could not simultaneously meet the requirements of sufficient construction time and high strength grade. Comparative Examples 4 and 5, using only compounded polyhydroxy alcohol retarders or sucrose, all showed insufficient strength even with the retarder's proportion in the rapid-hardening sulfoaluminate cement remaining constant. Comparative Examples 6 and 7, using a combination of two hydroxycarboxylic acid retarders (citric acid and sodium gluconate, or tartaric acid and sodium gluconate), both showed early false setting and significantly reduced strength. Compared to Example 1, Comparative Example 8, replacing the compounded polyhydroxy alcohol retarder with sucrose alone, also showed good retarding and strength effects, meeting certain construction requirements. However, the retarding effect of sucrose itself is unstable, and its performance is sensitive to temperature, requiring adjustment of the dosage in different seasons, which is not conducive to mass production.

[0089] Comparative Example 9 used a larger amount of lithium sulfate compared to Example 1, which significantly affected the construction time. In addition, the larger amount of lithium ions inhibited the normal formation of some hydration products, affecting the overall strength in the later stage.

[0090] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A dry powder mortar for cement-based inorganic terrazzo flooring, characterized in that, By weight, it includes the following components: The composition includes: 290 to 400 parts of rapid-hardening sulfoaluminate cement, 450 to 600 parts of aggregate, 60 to 100 parts of mineral filler, 8 to 15 parts of dispersible latex powder, 2.0 to 3.5 parts of water-reducing agent, 2.0 to 3.0 parts of retarder, 0.8 to 1.2 parts of defoamer, 0.3 to 0.8 parts of cellulose ether, 0.3 to 0.8 parts of early-strength agent, and 0 to 20 parts of pigment. The retarder includes a first retarder and a second retarder; the first retarder is a hydroxycarboxylic acid and / or its salt retarder; the second retarder is a compound polyhydroxy alcohol retarder, including sugar retarder, polyhydroxy alcohol retarder and additives.

2. The cement-based inorganic terrazzo floor dry powder mortar according to claim 1, characterized in that, By weight, it includes the following components: The composition includes 290 to 350 parts of rapid-hardening sulfoaluminate cement, 540 to 600 parts of aggregate, 80 to 100 parts of mineral filler, 10 to 15 parts of dispersible latex powder, 2.0 to 3.0 parts of water-reducing agent, 2.0 to 2.8 parts of retarder, 0.8 to 1.2 parts of defoamer, 0.3 to 0.6 parts of cellulose ether, 0.3 to 0.6 parts of early-strength agent, and 0 to 20 parts of pigment.

3. The cement-based inorganic terrazzo floor dry powder mortar according to claim 1, characterized in that, The hydroxycarboxylic acid and / or its salt as the first retarder is selected from any one or more of tartaric acid or its salt, citric acid or its salt, gluconic acid or its salt, malic acid or its salt, and salicylic acid; and / or The second retarder, by weight percentage, comprises 45% to 70% of a sugar retarder, 20% to 35% of a polyhydroxy alcohol retarder, and 10% to 25% of an additive. The sugar retarder is selected from any one or more of glucose, fructose, sucrose, lactose, starch, dextrin, and molasses; The polyhydroxy alcohol retarder is selected from any one or more of glycerol, sorbitol, xylitol, mannitol, polyvinyl alcohol, erythritol, and isomaltitol; The adjuvant is selected from one or more of dispersants, stabilizers, and synergists; and / or The percentage of the total weight of the retarder to the weight of the rapid-hardening sulfoaluminate cement is 0.6% to 0.9%; and / or The weight ratio of the first retarder to the second retarder is 1:(1.0 to 1.5), or optionally 1:(1.3 to 1.4).

4. The cement-based inorganic terrazzo floor dry powder mortar according to any one of claims 1 to 3, characterized in that, The first retarder is tartaric acid, citric acid, or sodium gluconate; The second retarder, by weight percentage, comprises 28% to 42% sucrose, 18% to 27% glucose, 14% to 22% sorbitol, 6% to 13% xylitol, 4% to 10% sodium tripolyphosphate, and 6% to 15% sodium lignosulfonate.

5. The cement-based inorganic terrazzo floor dry powder mortar according to any one of claims 1 to 3, characterized in that, The rapid-hardening sulfoaluminate cement is selected from white rapid-hardening sulfoaluminate cement or gray rapid-hardening sulfoaluminate cement; and / or The aggregate is selected from any one or more of manufactured sand, quartz sand, and river sand; optionally, the particle size of the aggregate is from 0.1 mm to 2.4 mm. Further optionally, the aggregate is quartz sand, and its particle size distribution, by weight, includes 150 to 200 parts of quartz sand with a particle size of 2.4 mm to 0.85 mm, 140 to 180 parts of quartz sand with a particle size of 0.85 mm to 0.425 mm, 130 to 170 parts of quartz sand with a particle size of 0.425 mm to 0.212 mm, and 50 to 100 parts of quartz sand with a particle size of 0.212 mm to 0.1 mm.

6. The cement-based inorganic terrazzo floor dry powder mortar according to any one of claims 1 to 3, characterized in that, The mineral filler is selected from any one or more of calcium carbonate powder, slag powder, talc powder, wollastonite powder, and mica powder; Optionally, the calcium carbonate powder is selected from any one or more of heavy calcium carbonate powder, light calcium carbonate powder, and limestone powder, and is further selected as heavy calcium carbonate powder; even further, the heavy calcium carbonate powder has a CaCO3 content of 95% to 99% and a particle size of 1 μm to 70 μm; Optionally, the slag powder is selected from S75, S95, or S105 grade slag powder, and may be selected as S95 grade slag powder; further optionally, the specific surface area of ​​the S95 grade slag powder is ≥400 m². 2 / kg, 28-day activity index ≥95%, moisture content ≤1.0%, flowability ratio ≥95%, particle size 1 μm to 60 μm; S95 grade slag powder, by weight, includes: 30 to 75 parts CaO, 28 to 38 parts SiO2, 8 to 18 parts Al2O3, 5 to 12 parts MgO, 0.1 to 2 parts MnO, and 0.1 to 3 parts sulfides.

7. The cement-based inorganic terrazzo floor dry powder mortar according to claim 6, characterized in that, The mineral filler is heavy calcium carbonate powder; or The mineral filler is heavy calcium carbonate powder and slag powder, with a mass ratio of 1:(0.5 to 2), which can be optionally 1:(0.8 to 1.2).

8. The cement-based inorganic terrazzo floor dry powder mortar according to any one of claims 1 to 3, characterized in that, The dispersible latex powder is selected from one or more of the following: vinyl acetate-ethylene copolymer, vinyl acetate, ethylene and higher fatty acid ethylene ester terpolymer dispersible latex powder, vinyl acetate and higher fatty acid ethylene ester copolymer dispersible latex powder, vinyl acetate, acrylate and higher fatty acid ethylene ester terpolymer dispersible latex powder; optionally, the dispersible latex powder is vinyl acetate-ethylene copolymer; and / or The water-reducing agent is selected from any one or more of polycarboxylate-based water-reducing agents, aminosulfonate-based high-efficiency water-reducing agents, aliphatic-based high-efficiency water-reducing agents, lignin sulfonate-based water-reducing agents, naphthalene-based high-efficiency water-reducing agents, and melamine-based high-efficiency water-reducing agents, and may be selected as a polycarboxylate-based high-efficiency water-reducing agent; and / or The defoamer is selected from any one or more of polysiloxane defoamers, polyether-type defoamers, polyether-modified silicone defoamers, tributyl phosphate, mineral oil-based defoamers, and alkynyl alcohol-based defoamers, and may be selected as a polyether-modified silicone defoamer; and / or The cellulose ether is selected from any one or more of methylcellulose ether, hydroxypropyl methylcellulose ether, and carboxymethylcellulose ether, and may be hydroxypropyl methylcellulose ether; and / or The early strength agent is selected from any one or more of lithium sulfate, lithium hydroxide, lithium carbonate, lithium silicate, lithium chloride, and aluminum sulfate, and may be lithium sulfate; and / or The pigment is selected from any one or more of titanium dioxide, iron oxide red, iron oxide yellow, iron oxide black, chromium oxide green, cobalt blue, ultramarine, manganese oxide, chromium oxide, ochre, Prussian red and mica; optionally, the pigment is titanium dioxide, wherein the TiO2 content is 90% to 98%.

9. The method for preparing cement-based inorganic terrazzo floor dry powder mortar for ground surfaces according to any one of claims 1 to 8, characterized in that, include: The early strength agent, cellulose ether, defoamer, retarder, water-reducing agent, dispersible latex powder, pigment and mineral filler are mixed evenly to obtain a premix; Mix the rapid-hardening sulfoaluminate cement, aggregate and the premix evenly; The cement-based inorganic terrazzo floor dry powder mortar for the ground is obtained.

10. A cement-based inorganic terrazzo floor dry powder mortar for ground use, comprising the cement-based inorganic terrazzo floor dry powder mortar according to any one of claims 1 to 8 or the cement-based inorganic terrazzo floor dry powder mortar for ground use prepared by the preparation method according to claim 9, and water; Optionally, the mass ratio of the cement-based inorganic terrazzo floor dry powder mortar to water is 1: (0.12 to 0.14).